Prospective Science Teacher TPACK Skills in Preparing the Lesson Plans - Dais Shopie Azizah; Dea Anjani Putri; Diah Mulhayatiah (Program Studi Pendidikan Fisika FKIP Universitas Riau, 2020)
Prospective teacher education is faced with the issue of integrating technological pedagogical and content knowledge (TPACK). Prospective teachers are expected to become teachers who are skilled at teaching effectively, mastering content, and are able to utilize technology in the learning process. The ability of TPACK for prospective science teacher can be seen from the preparation of a lesson plan, because there are elements of pedagogy, content, and technology in it, and it is seen from the suitability of the lesson plans with the implementation of learning by teachers in the classroom. Moreover, in implementing science learning, students must apply a scientific attitude to support learning so that students not only understand the theory but also master real concepts. The purpose of this study was to analyze the skills of prospective science teachers to apply TPACK in preparing lesson plans so that the weaknesses and strengths could be identified. The research method used is library research, by examining several sources related to the skills of prospective science teachers in implementing TPACK through the preparation of the lesson plan. The results of the research showed that some prospective science teachers still lacked skills in using integrated technology in the preparation of lesson plans, and the implementation of learning was not optimal so that it became a big challenge that science teachers had to face in the industrial revolution 4.0. Implementing TPACK in the preparation of the lesson plan can improve the quality of learning. The advantages produced can be seen from the effectiveness of the learning process provided through the use of technology in learning.